2022
DOI: 10.1063/5.0098917
|View full text |Cite
|
Sign up to set email alerts
|

A complex network framework for studying particle-laden flows

Abstract: Studying particle-laden flows is essential for understanding diverse physical processes such as rain formation in clouds, pathogen transmission, and pollutant dispersal. This work introduces a framework of complex networks to analyze the particle dynamics through a Lagrangian perspective. To illustrate this method, we study the clustering of inertial particles (small heavy particles) in Taylor–Green flow, where the dynamics depend on the particle Stokes number ( St). Using complex networks, we can obtain the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Clusterssmall conglomerations of particles such as molecules, nanoparticles, or colloidsare ubiquitous in natural and engineering systems. Because of their intermediate sizes between microscopic and macroscopic scales, clusters frequently serve as a bridge linking the dynamics of isolated particles and the properties of bulk matter and have attracted immense research interest due to various intriguing properties they impart to bulk materials. Particularly, the influence of clusters on the dynamics and mechanical properties of particle suspensions has been extensively studied for decades. Recent studies have shown that the emergence of a network-spanning cluster can significantly increase the rigidity of a system, i.e., the ability of the system to resist imposed perturbations. These percolating clusters are responsible for diverse phenomena ranging from the jamming transition of granular packings , to shear jamming and shear thickening of particle suspensions. …”
Section: Introductionmentioning
confidence: 99%
“…Clusterssmall conglomerations of particles such as molecules, nanoparticles, or colloidsare ubiquitous in natural and engineering systems. Because of their intermediate sizes between microscopic and macroscopic scales, clusters frequently serve as a bridge linking the dynamics of isolated particles and the properties of bulk matter and have attracted immense research interest due to various intriguing properties they impart to bulk materials. Particularly, the influence of clusters on the dynamics and mechanical properties of particle suspensions has been extensively studied for decades. Recent studies have shown that the emergence of a network-spanning cluster can significantly increase the rigidity of a system, i.e., the ability of the system to resist imposed perturbations. These percolating clusters are responsible for diverse phenomena ranging from the jamming transition of granular packings , to shear jamming and shear thickening of particle suspensions. …”
Section: Introductionmentioning
confidence: 99%